Staircase leading to the Porch of the Bhandasar temple - Temples of India Project Team (Jio Institute, 2024)
This is the main entrance to the Bhandasar Temple. The staircase leads to a porch of the temple through which one enters the main temple. Though the temple has a staircase flanking the main entrance, this entrance seen in the picture is the principal ingress to the temple. Only the pillars of the front porch are painted in white and decorated in floral motifs.